PENYULUHAN TENTANG PENGELOLAAN SAMPAH 3R (REDUCE, REUSE, RECYCLE) DI KELURAHAN SEI LAIS KOTA PALEMBANG - Hestirinaih, Deby Chintia; Asteriniah, Femi; Herfriady, Herfriady (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2023)
Community service in its implementation cannot be separated from the two other parts, namely Education and Teaching and Research. This community service was motivated by activities in Sei Lais Village, Kalidoni District, Palembang City. After conducting a survey in Sei Lais Village, Kalidoni District, RT 12 and RT 13 identified problems regarding waste management. Therefore, it is necessary to find a solution to reduce the amount of waste piled up. The right way is to run a waste management program with the